Compensation for cultural untranslatability in the novel Siddhartha / Wong Aw Lian Chee - Wong Aw, Lian Chee (2016)

(untitled)
Background of the paper constitutes conclusive research on the theoretical basis of translation, the method of compensation for the cultural untranslatability of translation, and translation techniques. This research uses textual analysis to examine the method of compensation in the novel Siddhartha, when translated into English and Chinese. The findings of this research were compiled and discussed in the broad area of impact regarding cultural untranslatability, and the solution to cultural translation. From this work, it is evident that the use of this technique is an effective method for analysing cultural untranslatability.